Research capacity development in South African higher education: an analysis of the challenges and opportunities presented by the new generation of academics programme - Magabane, Mmamajaga Angeline (My University, 2022)
Investing in the development of research capacities among young academics from designated groups has become a central part of planning for the South African government and universities. Research capacity development initiatives have therefore increased significantly over the years, with most universities initiating multi-faceted approaches to providing training for research staff and funding through research grants. This study explored the concept of research capacity development in South African higher education by investigating and analysing the challenges and opportunities associated with the implementation of the New Generation of Academics Programme (nGAP) in selected South African universities. It was noted that these opportunities and challenges could be either constraining or enabling for the nGAP programme in general, as well as for participants in the study, who are nGAP lecturers, mentors and managers. Determining the factors that enable or constrain the implementation of the nGAP was achieved by exploring the motivation of participants to be part of the nGAP, examining the mechanisms employed by participating universities to support the programme and the extent to which these constrain or enable its implementation; as well as investigating the views and experiences of participants about the implementation of the different components of the nGAP in their respective universities. This study is the first qualitative research to investigate and analyse the factors that affect the implementation of the nGAP at institutional levels, from the point of view of the lecturers, managers and mentors participating in the programme. This is a timely study, given that the nGAP is in its sixth year of existence, which marks the conclusion of training for the first cohort participating in the programme. The programme was initiated in 2016 to recruit, develop and retain young and emerging academics from designated groups across the twenty-six universities. The nGAP has the long-term goal of transforming the academic staff demographics in the South African higher education sector. The study is located within the interpretivist paradigm, therefore qualitative research methodologies and instruments were applied. The sample for the study comprised eight lecturers, six mentors and five managers participating in the nGAP at the eight public universities. A total of nineteen semi-structured interviews were conducted with participants, with the purpose of understanding their views and experiences, and the contexts within which they operate, as well as how the implementation of nGAP functioned. The study was limited because it only focused on the implementation of the nGAP as one of the many strategies for developing research capacities in South African public higher education institutions. Although there are other research capacity development programmes implemented by universities, the majority are not government sponsored and are therefore not very well known. It would therefore have been a daunting task to even begin to expand the focus of such programmes, especially considering the time limitations and financial constraints of the study. This limitation provides an opportunity for further research to be conducted on how these other programmes compare to the nGAP, and how their implementation and support vary at different universities. Only eight universities out of the 26 that participated in the implementation of the nGAP took part in the study. The rich narrative data produced by the study was analysed through the lens of the capability approach, which provided a structure for reflecting on factors associated with the participants’ environments and circumstances that could suggest policies for improving the implementation of the nGAP at institutional and national level. Evidence produced by the study indicates the nGAP is a valuable programme, based on sound principles and good intentions. However, its implementation at the institutional level is both constrained and enabled by several factors at the individual and institutional levels. These tend to affect the experiences of the three categories of participants in the study, both negatively and positively. These issues include institutional cultures and climate, the university processes and systems, the contradiction between national policy and practices at institutional level, the lack of policy to guide mentoring for the programme and the inflexible implementation of the different features of the programme. The findings are intended to contribute towards a better understanding of the challenges and opportunities associated with the implementation of the nGAP. The study’s contribution to theory is through its conceptualisation of the nGAP as a research capacity development programme, with its implementation taking place at three interconnected and interrelated levels: individual, institution and government. The study was also intended to influence policy and practice in government and in the higher education system, in order to strengthen the nGAP implementation processes. Mentoring was one aspect of the nGAP that featured strongly in the narratives of the three categories of participants, particularly the lectures and mentors. It was found to be constrained, mainly by the lack of policy or any other guiding framework. As part of its contribution to new knowledge, the study proposes a model for the development of the nGAP mentoring framework to improve mentoring practices in the programme. It is hoped that this will help to develop a mentoring policy/ framework for the nGAP would strengthen the debate around mentoring in the South African higher education sector.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Humanities, School of Education, University of the Witwatersrand, 2022